The effect of type II toxin-antitoxin systems on methicillinresistant Staphylococcus aureus persister cell formation and antibiotic tolerance - Hosseini Mandana (Acta biologica Szegediensis, 2021)
Persister cells are defi ned as a subpopulation of bacteria in a dormant state with the ability to reduce bacterial metabolism and they are involved in antibiotic tolerance. Toxin-antitoxin (TA) systems have been previously suggested as important players in persistence. Therefore, this study aimed to study the involvement of TA systems in persister cell formation in methicillin-resistant Staphylococcus aureus following antibiotic exposure. Using TADB and RASTA database, two type II TA systems including MazF/MazE and RelE/RelB were predicted in S. aureus. The presence of these TA genes was determined in 5 methicillin-resistant S. aureus isolates and the standard strain S. aureus subsp. aureus N315 using PCR method. To induce persistence, isolates were exposed to lethal doses of ciprofl oxacin and the expression of the studied TA system genes was measured after 5 h using Real-Time PCR. According to our results, all the studied isolates harbored the TA system genes. S. aureus was highly capable of persister cell formation following exposure to sub-MIC of ciprofl oxacin and RT-qPCR showed a signifi cant increase in the expression of the MazEF and RelBE loci, indicating their potential role in antibiotic tolerance. Considering the importance of antibiotic tolerance, further studies on persister cell formation and TA systems involved in this phenomenon are required to effi ciently target these systems.